Between-ward disparities in colorectal cancer incidence and screening in Washington DC - Sharmila Chatterjee; Amit Chattopadhyay; Paul H. Levine (Springer, 2015)
This study aims to investigate the incidence and determinants of colorectal cancer (CRC) and its screening in District of Columbia (DC), and identify modifiable risk factors. Data (2000-2009) from the DC Cancer Registry, Behavioral Risk Factor Surveillance System (BRFSS-DC) and Surveillance Epidemiology and End Results (SEER) were used to estimate CRC incidence in eight DC Wards. Risk factors and CRC screening were analyzed using uni-, bi-, and multivariable statistical methods with survey procedures in SAS (version 9.2) including binary, unconditional multivariable logistic regression analysis. Factors measured included stage of diagnosis, age, gender, race/ethnicity, smoking, alcohol, exercise, body weight, health insurance, education, employment, and income. Over the study time, CRC screening increased from 48.4% to 68.6%. Mean age at diagnosis was 67 years. CRC incidence is high in DC. Furthermore, CRC incidence rates in DC below 50 years age were higher than the SEER18 average. Disparities exist between CRC incidence and screening among DC Wards. Identified risk factors for CRC are smoking, obesity, and low physical activity; screening was less prevalent among the uninsured and low socio-economic group. Local variations in CRC occurrence exist and may vary from average national experiences. Identification of local regions which vary from national trends in disease occurrence is important for comprehensive understanding of the disease in the community.